CRITICAL REFLECTION ON A SPECIFIC TEACHING CONTEXT - Sri Agriyanti (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2017)
The goal of this paper is to critically reflect the use of target language in the classroom can improve students’ proficiency of the language as they will more familiar with the sound and the linguistics features. And also that the students’ mother tongue could be used as resources for teaching and learning because English is taught in classes where the students and teachers share the same mother tongue. This Paper will answer questions about should weuse of mother tongue in EFL classroom? Should we teach English as an international Language or English as Foreign Language? And Should English taught by grammar translation approach or using communicative approach?